MUSIK ODROT DI KABUPATEN PONOROGO - Hengki Triprasetyo (SELONDING, 2017)
Odrot music is the art of music featured in Ponorogo, existing end centuries of Dutch colonialism in Indonesia, but its development was started in 1958. From then on stand several music groups Odrot, but that survive today are a group of music Odrot Kelana Ria. Although there are other groups who also manages Music Odrot, but the players invited players in Kelana group Ria. Music Odrot is a musical ensemble consisting of instruments trumpet, Euphonium 1, Euphonium 2, flugel, sousaphone (which by the player music Odrot called a piston, tenor 1, tenor 2, kaltu, bass), drums, kendang ciblon, ketipung dangdut, jidor and cer, keyboard and electric bass.Odrot Music initially brought the songs of preaching Islamic nuance. Furthermore, Odrot music was developed in accordance with the times so that the songs were not limited to propaganda songs where tailored to the needs of supporters. This study aimed to describe a way of presenting Odrot music and explain its function in society in detail. Odrot Music ensemble distinguished by traditional and modern terms: so-called traditional because of the instruments used is a piston, tenor 1, tenor 2, kaltu, bass, drums, kendang ciblon, ketipung dangdut, jidor and cer; called modern because coupled with keyboard instruments and electric bass. If the ensemble Odrot Music brings the songs styles (langgam), the instruments which are used namely kendang ciblon, while dangdut songs accompanied by ketipung dangdut.There is a basic song which (if not in special circumstances) is always played the name of that song is Ponoragan Kebo Giro. In addition, this song further characterize Odrot. Ponoragan songs Kebo Giro consists of 8 (eight) bars are played repeatedly in accordance with the cue trumpet. The song is sung to the rhythm of the Odrot's mars and traditional. Therefore, the ordot main function is as an entertainment in addition to other functions as an aesthetic presentation, the physical response, local cultural identity, informal educational facilities, media propaganda, cultural continuity, communication, and community integration.